MUJAHID VERSUS TERORIS - Ilyas Supena (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2012)
War of opinions about the victims of Bali blast in public media was observed in two national newspaper, Republika and Kompas. Although the both newspapers are of national level, but in fact the request to be objective in informing opinions toward all community class and groups is some-thing difficult to achieve. This is based in the idea that every communication action contains any interrest—the more in mass media. In the side of Republika the execution of Amrozi seen as universal humanity problem, meanwhile for Kompas it only seen as local case that is related to the persons involved in the incident. Republika provides enough room for developing the discourse on jihad and terorism in order to build a counter opinion on the news that oftenly offense Amrozi meanwhil Kompas convines it self for not to involve in the discourse of theology.***Perang opini tentang korban ledakan Bali di media massa diamati di dua surat kabar nasional, yaitu Republika dan Kompas. Walaupun kedua surat kabar tersebut berskala nasional, namun dalam kenyataannya tuntutan untuk obyektif dalam menyampaikan opini kepada masyarakat merupakan hal yang sulit. Ini didasarkan pada gagasan bahwa setiap tindakan komunikasi mengandung kepentingan. Di pihak Republika ekskusi Amrozi dipandang sebagai masalah kemanusiaan universal, sementara bagi Kompas ekskusi tersebut hanya dipandang sebagai kasus lokal yang terkait dengan pribadi yang terlibat dalam kejadian tersebut. Republika memberikan ruang yang cukup bagi pengembangan diskursus mengenai jihad dan terorisme dalam rangka untuk membangun opini imbangan terhadap berita-berita yang seringkali menentang Amrozi sementara Kompas membatasi diri untuk tidak masuk ke dalam diskursus teologi.